Experience and Perception of Psychosocial and Environmental Problems among Migrant Laborers Returned from the Gulf and Malaysia - Bhattarai, Prem Nath; Dhakal, Sandesh (Patan Pragya, 2023)
Migration to India has always been a common trend in Nepal for a historical period. However, in recent years, the destinations of labor migrants have expanded beyond India to many other countries. Gulf countries and Malaysia are some of the major attractions of Nepalese migrant laborers who are unskilled or semi-skilled. Before labor migrants depart, various provisions evaluate their physical health. However, mental health issues, which should have equal importance, are apparently neglected so far by concerned authorities. This study investigates the pre-migration, migration, and post-migration psychosocial and environmental issues of migrants and their in[1]depth perspective of the causes and effects of these problems. These problems are a fundamental component of mental health disorders. A mixed method design was adopted to explore the phenomenon - a checklist was used to collect quantitative data on the experience of psychosocial problems, and in-depth interview sessions were conducted to explore participants' perceptions further. The results revealed that psychosocial problems were prevalent in all three phases - before, during, and after migration. The result reveals that psychological problems associated with economic hardships were more dominant in the pre-migration phase and occupation/job[1]related psychological problems were more paramount during and after the migration phase. The detailed findings are further analyzed and discussed.